Structural check of a steel through truss bridge - Dickens, Loren E., III (Kansas State University, 2008)
The Abilene & Smoky Valley Railroad Association offers train excursions to sightseers wishing to see historic Abilene and natural Kansas scenery. Currently, a diesel powered ALCO locomotive is used to pull the passenger cars. They wish to use a 1919 Baldwin steam locomotive in the future. Part of the excursion includes a slow crossing of the Smoky Hill River over a two-span steel truss bridge. The company approached the Kansas State University Civil Engineering Department with the task of performing a structural check of the bridge. By using the Baldwin locomotive, the bridge is required to support much larger loads than when the diesel engine is used. First, a basic visual inspection and site visit of the bridge was performed. The inspection was not thorough, but was used to familiarize the team with the bridge and its components. Using the inspection and data supplied, a structural analysis was performed using the software, RISA. After completion of the analysis for both loading situations, the resulting stress increases were calculated. Other calculations performed include buckling loads of the compression members, deflections of the bottom chord and stresses in some of the connections. After completion of the analysis and calculations, large increases in member stress were found. For most of the members, the increase of live loads stress was between 80% and 100%. The largest stress found due to the dead and live load, which was under 15 ksi, occurred in the bottom chord for the steam locomotive loading situation. Some truss members experienced stress reversal, but relatively low values were noted. Deflection calculations for the two loading situations yielded similar results to the stress calculations. Again, an increase in deflection between 80% and 100% was found for the joints located on the bottom chord. It is recommended that a more detailed inspection and a more thorough analysis of the connections, supports, piers, and foundations be performed before the heavier locomotive is used.
Keywords: Bridge; Truss; Structural analysis; Steel; Engineering, Civil (0543)